Telaah Transaksi Go-Food Dalam Perspektif Akuntansi Syariah (Studi Kasus User & Kantor Go-Jek Gorontalo) - Jonly Umar (AKASYAH: Jurnal Akuntansi, Keuangan dan Audit Syariah, 2021)
The speed of the development of the times gives so much convenience in mengaskes everything. One of the convenience is in bermuamalah, especially economic transactions. Islam certainly does not stem the current rate of development of the times, but Islam limits the rules in accordance with the Qur'an and Sunnah. In this research, lifting one product from a platform, Go-Jek, with its GoFood product. This research is expected to provide a clear picture of Go-Food transactions viewed in an Islamic perspective. The purpose of this study is to find out how accounting practices and contracts that occur in Go-Food. The research method used is descriptive qualitative research method. With data sources from interviews and related literacy source studies. The results of the study prove that the Go-Food transaction is seen from the overall relationship of all related parties, dominantly included in the Ijarah contract (lease).